PREVALENCE OF PAN MASALA USE IN A COASTAL POPULATION OF KERALA - Sandhya G.I; S.Sunil and Bennet Abraham (Oral Max Path J, 2013)
Back ground: Oral cancer remains the most common cancer reported in Indian males. Tobacco smoking , h alcohol and pan masala use are considered as the major risk factors for oral cancer. Pan masala use has become a common culture in Indian community. Many studies have been conducted among fisher folks regarding the prevalence of pan masala use. Objectives: To determine the prevalence of panmasala use among coastal population and factors related to it. Methodology :A community based cross-sectional survey was carried out among 1076 randomly selected male fishermen aged 25 years and above in three randomly selected coastal villages of Thiruvananthapuram district. Chi-square test and standard deviation and percentage values were used as the statistical tool. p value less than 0.05 is considered as significant. Result : The prevalence of pan masala use was 28.3%.panmasala use is highest among the men of age group of 45-50 years. The mean age of onset of pan masala use was 17.7(standard deviation [sd] 9.7).Only 40.4% of the study population had awareness about the fact that pan chewing can cause oral cancer . 87.2% subjects agreed that panmasala which they consume regularly contain tobacoo. The factors which favour pan masala use were(p<0.05) low education, ageing and low awareness . Conclusion : The present study has identified very high level of panmasala use among young fishermen and easily onset of these habits. It has also been noticed that reported oral morbidities are high among pan masala users. The study highlights the need of an extensive oral cancer screening and awareness programmes against pan masala use in the coastal areas for early detection and prevention of tobacco induced oral potentially malignant disorders and oral cancer.